Hukuman Mati Bagi Murtad Perspektif Syekh Ali Jum'ah - M. Sholahuddin Al Ayyubi; Try Heni Aprilia (Syariah: Journal of Fiqh Studies, 2023)
The existence of Islam as a religion, clean from all forms of coercion, including embracing religion, is shaken by the concept of fiqh, which punishes death for apostasy. In addition, the law is claimed to be part of the ijma 'ulama. This journal attempts to unravel the death penalty polemic using Shaykh Ali Jumah’s approach. The research model used in this study is based on a qualitative literature review. The results of this study indicate that the death penalty for apostasy is not based on a person's attitude toward choosing to leave Islam. However, other attitudes carry the consequences of death, such as ḥirabah (fighting Muslims) and/or the betrayal of Islam (mufāriq lil jamā'ah). In this case, the claim of ijma deserves to be doubted if one sees a motive for leaving Islam simply because of disbelief. This was because the two procedures were performed by Rasulullah SAW. ever ordered his companions to kill the perpetrators of apostasy, not solely for the motives of kufr. Instead, there is a form of betrayal. In addition, ijma’s claim regarding the consequences of death for apostates is strongly suspected to apply the pattern of saddan li al-dzariah or saddan li al-bab. This is meant to close the door to the opportunity for religion to be harmed by apostates.